IPCC and the Deep Sea: A Case for Deeper Knowledge - Levin, Lisa A. (Frontiers in Climate, 2021)
IPCC reporting culture and structure leads to a failure to highlight potential vulnerabilities and risk in areas where research is largely absent. Nowhere is this more obvious than in treatment of the deep ocean (waters below 200 m), where climate research is in its infancy, but human exploitation of resources is on the rise. Understanding climate-induced changes in deep- sea environments, ecosystems and their services, including carbon cycling and climate regulation, is fundamental to future ocean sustainability and to decisions about active climate remediation.